2018
DOI: 10.1590/1980-5373-mr-2017-0779
|View full text |Cite
|
Sign up to set email alerts
|

Study on Effect of EAFD Particulate Reinforcement in AA7075 Aluminum Matrix Composites

Abstract: Eletric arc furnace dust is dangerous solid waste that is generated in steel manufacturing processes. The utilization of the dust from these industries avoids disposing it into industrial waste landfills and saves costs. In this study, an attempt has been made to fabricate aluminum matrix composites reinforced with EAFD particulate, throught the conventional powder metallurgy technique. Al-5%EAFD proposed was then compared to the AA7075 alloy, manufactured under the same conditions. According to the results ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 35 publications
(54 reference statements)
0
10
0
Order By: Relevance
“…The crystallite size is equal to about 61 and 45 nm and strain is about 0.07 and 0.12%, for AA7075 and AA7075-M, respectively. Table 2 also shows the estimated value of the density of dislocations for each sample, which was obtained using Equation (7). Comparing values for AA7075 and AA7075M highlights that milling considerably increases the density of dislocations [34,40].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The crystallite size is equal to about 61 and 45 nm and strain is about 0.07 and 0.12%, for AA7075 and AA7075-M, respectively. Table 2 also shows the estimated value of the density of dislocations for each sample, which was obtained using Equation (7). Comparing values for AA7075 and AA7075M highlights that milling considerably increases the density of dislocations [34,40].…”
Section: Resultsmentioning
confidence: 99%
“…The powder was ball-milled in isopropyl alcohol for 1 h with 2 wt.% stearic acid (CH 3 (CH 2 ) 16 COOH). Milling was performed with a ball to powder weight ratio of 10:1 [ 7 , 25 ]. The raw and ball-milled powders will be referred to hereafter as AA7075 and AA7075-M, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, EAFD is classified as hazardous by several agencies, including the Brazilian Association of Technical Standards [ 4 ], the Environmental Protection Agency [ 5 ], and the European Waste Catalog [ 6 ], due to its content of metals such as zinc, cobalt, copper, lead, and cadmium. Therefore, despite it being considered a renewable resource [ 7 ] and a secondary raw material [ 8 ], finding a suitable use for the EAFD represents a strong challenge, and some studies have reported recycling it as filler in composite materials with polymer [ 9 , 10 ], ceramic [ 11 ], cement [ 12 ], concrete [ 7 ], and metal matrix [ 13 , 14 , 15 ]. Regarding the latter, aluminum matrix composites (AMCs) in particular are of great interest because alloys such as the 7075 aluminum alloy (AA7075) exhibit characteristics (low density, high strength-to-weight ratio) that are of great importance, including for applications in the automotive, aeronautics, and naval industries.…”
Section: Introductionmentioning
confidence: 99%
“…Many compounds have been used for the reinforcement of AA7075, including SiC [ 16 , 17 , 18 , 19 ], TiC [ 17 , 20 ], B 4 C [ 21 , 22 ], Zr [ 23 ], Ag [ 24 ], TiO 2 [ 25 ], Al 2 O 3 [ 26 , 27 ], and reduced graphene oxide [ 28 ]. However, such compounds may themselves be of high value and therefore expensive, whereas the use of agricultural [ 27 , 29 , 30 , 31 , 32 , 33 , 34 ] and industrial waste [ 13 , 14 , 15 , 35 ] as reinforcement in AMCs is still little explored. The aim of this work is to investigate AA7075-EAFD composites with different EAFD contents and two different particle size ranges.…”
Section: Introductionmentioning
confidence: 99%